Spectral frequency and space domain coordination for IMT-advanced coexistence with point-to-point service - A. Shamsan, Zaid (Institute of Electrical and Electronics Engineers, 2009)
Coexistence of various wireless systems may cause frequency intersystem interference problems. Consequently, frequency sharing studies play a very important task in order to use limited spectrum resources efficiently. Because an International Mobile Telecommunication-Advanced (IMT-Advanced) systems are going to use 3500 MHz according to World Radiocommunication Conferences 2007 (WRC-07) decision along with point-to-point Fixed Wireless Access (FWA) system, which currently allocated in the same band, the frequency sharing between IMT-Advanced and FWA is essential. This paper investigates the spectrum sharing requirements in different terrestrial areas using interference to noise ratio criterion. Three methods of investigation of the interference, co-channel, null-guard band, and adjacent channel, have been proposed to investigate the phenomenon in the frequency and space domains to obtain correlation between the minimum separated range of base stations antennas and the frequency separation. Off-axis angles alignment is also proposed to decrease the required separation distance for acceptable coexistence between systems.